PROGRAM PENGUATAN PELAJAR PANCASILA DENGAN MEWUJUDKAN SEKOLAH RAMAH ANAK ANTI BULLYING - Maslahah, Wafiyatu; Lestari, Rr. Hesti Setyodyah; Kartikaningrum, Juwita; Galih, Sofyan; Rachman, Faradiba; A, Nadhiv Ulvia (LP2M STP Mataram, 2023)
A school is a structured educational institution tasked to create generations of noble people. This corresponds to one of the Pancasila student profile competencies. An anti-bullying child-friendly school socializing program was offered at SDN 02 Putukrejo Village, Kalipare District, Malang Regency. This outreach activity at SDN 02 Putukrejo Kalipare has the following objectives: 1.) raise awareness of bullying. 2.) encourage children to love and act together. 3.) eliminate instances of bullying, and 4) create a safe and comfortable school. This community service activity will be implemented through the following steps: 1.) Carrying out a preliminary study at SDN 02 Putukrejo, Kalipare by exploring issues involving the student profile of Pancasila, 2.) Coordinating with the school regarding solutions to existing problems, 3.) Organizing socialization activities in child-friendly schools to combat bullying, 4.) collecting information regarding the benefits of socialization activities for the school, namely teachers and students. The outcomes of socializing activities include 1.) students becoming aware of the effects and remedies to bullying; 2.) students becoming concerned and helping one another, and 3.) students becoming concerned and helping one another. 3.) There is no longer any bullying or harassment at school, and 4.) school becomes more comfortable and safe.